Contemporary musical film - Donnelly, K. J. (Kevin J.); Carroll, Beth (Lecturer in Film and Literature); Hatch, Craig; Donnelly, K. J. (Kevin J.); Dubowsky, Jack Curtis; Carroll, Beth; Fremaux, Stephanie; Bunch, Ryan; Haworth, Catherine; Sapiro, Ian; Baschiera, Stefano, 1977-; Decker, Todd R. (Edinburgh University Press, 2017)
This edited collection looks closely at the range and scope of contemporary film musicals, from stage adaptations like Mamma Mia! (2008) and Les Miserables (2012), to less conventional works that elide the genre, like Team America: World Police (2004) and Quentin Tarantino's Kill Bill (2003/04).
Keywords: Musical films -- History and criticism.; Motion pictures and music.; Films musicaux -- Histoire et critique.; PERFORMING ARTS -- Reference.; ART -- Criticism & Theory.; Motion pictures and music; Musical films; Filmmusical; Musical; Musikfilm; Performing Arts.; Criticism, interpretation, etc.